Unveiling the synergy of sustainable manufacturing practices and lean for sustainable manufacturing competitiveness - Gupta, Sumit; Joshi, Deepika; Jamwal, Anbesh; Bhanot, Neeraj; Jagtap, Sandeep (Discover applied sciences, 2025)
The present study investigates the integration of Lean and Sustainable manufacturing (LSM) practices to improve the market competitiveness of Indian manufacturing organizations. The study aims to explore the critical role of stakeholder commitment to drive both sustainable manufacturing and lean practices with their impact on manufacturing competitiveness. In the study a survey-based approach was used, the data was collected from 152 Indian manufacturing firms and analyzed using Principal component analysis (PCA) and Structural equation modelling (SEM) approach with IBM SPSS and AMOS software. The sampling approach focused on the consideration of medium and large enterprises of India across various sector using the structure questionnaire to assess the key constructs such as: stakeholder commitment, lean practices, and sustainable manufacturing. The result of the study reveals that stakeholder commitment significantly influences the adoption of both sustainable and lean manufacturing practices which help to drive manufacturing competitiveness. The SEM analysis conducted in the study reveals that there is structural relationship between the variables which further provides the evidence that organization ability to integrate lean and sustainable manufacturing practices improves the market competitiveness in dynamic business environment.